PENGABDIAN KEPADA MASYARAKAT DALAM PROGRAM BEDAKAN; REDESAIN IDENTITAS JENAMA DAN KEMASAN PRODUK KOPI SRIKANDI - Erlyana, Yana; Jeremy, Jeremy (Universitas Bunda Mulia, 2023)
One of the world's most agricultural products is coffee. Apart from being the largest coffee producer in the world, Indonesia also offers a variety of coffee thanks to its soil fertility. Considering the problems above, this activity aims to redesign Srikandi's coffee from Carangsari village through graphic design. One of the Balinese Robusta coffee producers owned by Mrs. Ni Ketut Wakul who has been operating in Carangsari Village since 1990. In implementing this community service, the design thinking method is used in five steps, namely: empathize, define, ideate, prototype, and test stages. The design process, according to the design thinking method is considered very good in identity development and package redesign because in it brand owners can participate in project development so that the designs developed not only have a fair value but also have a fair value. . emotional connection with the trademark owner. This activity has good consequences for brand owners, where brand owners can add value to their products in the future with a new identity and packaging.